2019
DOI: 10.22159/ijap.2020v12i2.36462
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and Characterization of Chitosan-Based Nanoparticles Containing Methylprednisolone Using Box-Behnken Design for the Treatment of Crohn’s Disease

Abstract: Objective: The present research was designed to produce methylprednisolone containing chitosan-based nanoparticles using Box-Behnken Design (BBD) and Response Surface Methodology (RSM) for optimization. Methods: Nanostructures were prepared using the ionic gelation method with screened process parameters. According to the design, methylprednisolone chitosan-based nanoparticles (MCSNPs) were optimized using factors like methylprednisolone concentration, stirring speed and temperature whereas particle size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…Different concentration of three CSPP (as shown in table 1) viz., A = polyacrylamide with their low (1.4 g), medium (2.1 g) and high level (2.8 g) and B = ceric ammonium nitrate with their low (25 mg), medium (50 mg) and high level (75 mg) and Temperature low (40 °C), medium (50 °C) and high level (60 °C) were selected. Box behnken design was applied using design expert software [13,14] (version 7.0, Statease. Inc, USA) and the polynomial equation generated was given below:…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Different concentration of three CSPP (as shown in table 1) viz., A = polyacrylamide with their low (1.4 g), medium (2.1 g) and high level (2.8 g) and B = ceric ammonium nitrate with their low (25 mg), medium (50 mg) and high level (75 mg) and Temperature low (40 °C), medium (50 °C) and high level (60 °C) were selected. Box behnken design was applied using design expert software [13,14] (version 7.0, Statease. Inc, USA) and the polynomial equation generated was given below:…”
Section: Experimental Designmentioning
confidence: 99%
“…. In the above polynomial equations, the magnitude of coefficients revealed that the concentration of initiator (B) had maximum effect on all the three parameters [13,14].…”
Section: Fig 1: Process For Microwave-based Graftingmentioning
confidence: 99%
“…Where Y is the measured response of the dependent variables, β0 is the intercept, β1-β9 are the regression coefficients computed from the observed experimental values of Y. X1, X2 and X3 are the coded value of the independent variables. X1 X2X3 (a, b = 1, 2, 3) and X 2 i (i = 1, 2, 3) represent the interaction and quadratic terms, respectively [16,17]. The graft copolymer of karaya with acrylamide was characterized by FTIR, DSC, XRD and SEM and % grafting (%G) and % grafting efficiency (%GE) were calculated by using following equations [18]:…”
Section: Experimental Designmentioning
confidence: 99%
“…The active substance, Dimethyl Fumarate, is thought to work by activating a protein called 'Nrf2' that regulates certain 'antioxidant' genes involved in protecting cells from damage of various form of multiple sclerosis [6]. Dimethyl fumarate is a white crystalline powder, nonhygroscopic [7,8] BCS class 1 (highly soluble and highly permeable) [7,8]. The structural formula of the Dimethyl Fumarate has been given in Figure 1 [9].…”
Section: Introductionmentioning
confidence: 99%